Anton Wagner, The Spiritualist Prime Minister, Vol. I, Mackenzie King and the New Revelation, and Vol. II, Mackenzie King and His Mediums - Hubner, Brian (Archivaria, 2026)
The Spiritualist Prime Minister, Vol. I, Mackenzie King and the New Revelation, and Vol. II, Mackenzie King and His Mediums. Anton Wagner. Guildford, UK: White Crow Books, in association with the Survival Research Institute of Canada, 2024. 390 pp. and 386 pp. 9781786772640 and 9781786772664